Validitas dan Praktikalitas Pengembangan Multimedia Interaktif Berbasis Macromedia Flash 8 Pada Pembelajaran Tematik di Kelas IV Sekolah Dasar Kota Padang - Nadia Oktavia; Desyandri Desyandri (Universitas Negeri Padang, 2020)
This research aims to describe the produce interactive multimedia based on Macromedia Flash 8 in grade IV elementary school that meet valid dan practical criteria. This type of research is development research The development research model used is the ADDIE development model which has five-stage namely Analysis, Design, Development, Implementation, and evaluation. Data collection using research instruments including validation sheets (material expert, linguist, and media/graphics expert) and practice sheets (questionnaire responses from teacher and student). The result of the development of interactive multimedia through the validation stages of the material aspect obtained a value of 92%. In the language aspect, it scores 90% and the media/graphic aspect gets a score of 92%. While from the questionnaire student and teachers both obtained average scores of 86%. Based on these results it can be concluded that interactive multimedia in class IV learning based on Macromedia Flash 8 is very valid and very practical to use as a support for learning.